Termination of transcription by bacteriophage T3 RNA polymerase: homogeneous 3'-terminal oligonucleotide sequence of in vitro T3 RNA polymerase transcripts. - Majumder, H K (1979)
RNA was synthesized in vitro from a T3 DNA template by T3 RNA polymerase and subsequently separated into seven discrete size classes (molecular weights ranging between 0.21 x 10(6) and 6.2 x 10(6)) by electrophoresis in polyacrylamide slab gels. RNase T1-generated 3'-terminal oligonucleotide fragments were then selectively isolated from either the unfractionated total RNA or the gel-purified specific transcripts by chromatography on columns of dihydroxyboryl-cellulose. Sequence analysis of these oligonucleotide products indicated that the unfractionated transcripts as well as all the individual major RNA species examined had a unique sequence, (Gp)UpUpUpUpUpGOH, at their 3' termini. The specificity of this sequence, as well as the total lack of any sequence heterogeneity at the ends of these transcripts, indicates a high degree of specificity of termination during transcription in this system.